Compressive and fatigue behavior of beta-type titanium porous structures fabricated by electron beam melting. (March 2017) - Liu, Y.J.; Wang, H.L.; Li, S.J.; Wang, S.G.; Wang, W.J.; Hou, W.T.; Hao, Y.L.; Yang, R.; Zhang, L.C.
Abstract: β-type titanium porous structure is a new class of solution for implant because it offers excellent combinations of high strength and low Young's modulus. This work investigated the influence of porosity variation in electron beam melting (EBM)-produced β-type Ti2448 alloy samples on the mechanical properties including super-elastic property, Young's modulus, compressive strength and fatigue properties. The relationship between the misorientation angle of adjacent grains and fatigue crack deflection behaviors was also observed. The super-elastic property is improved as the porosity of samples increases because of increasing tensile/compressive ratio. For the first time, the position of fatigue crack initiation is defined in stress-strain curves based on the variation of the fatigue cyclic loops. The unique manufacturing process of EBM results in the generation of different sizes of grains, and the apparent fatigue crack deflection occurs at the grain boundaries in the columnar grain zone due to substantial misorientation between adjacent grains. Compared with Ti-6Al-4V samples, the Ti2448 porous samples exhibit a higher normalized fatigue strength owing to super-elastic property, greater plastic zone ahead of the fatigue crack tip and the crack deflection behavior. Graphical abstract: Image 1 Highlights: The super-elastic property is improved with increasing porosity of Ti2448 porous samples. The position of fatigue crack initiation on the strain curve is defined. The unique EBM-produced microstructure leads to apparent fatigue crack deflection occurring at columnar grain boundary. Ti2448 porous samples display only half of the Young's modulus of Ti-6Al-4V porous samples at same fatigue strength level.